Active metasurface in reflection manner for generation of reconfigurable OAM vortex beams - Yunfei Liu; Yueyi Yuan; Qun Wu; Kuang Zhang (Journal of Information and Intelligence)
In this paper, we proposed an active metasurface in reflection manner that can generate reconfigurable OAM vortex beams with high purity in the X-band. The metasurface has a high reflectance of 0.94 and achieves a phase coverage of 320° between 9.8 ​GHz and 11 ​GHz. Then, by encoding the phase distribution of the meta-atoms, various OAM vortex beams including ±1, ±2, ±3, and ±4 orders are generated, where the purity of all modes can be above 70%. Moreover, the metasurface can also deflect the OAM beam with a certain angle while maintaining high purity, which can be applied to reduce the influence of the alignment deviation between transmitting and receiving antennas during the communication processes. As a validation, the metasurface composed of 30 ​× ​30 meta-atoms is fabricated and measured. Both simulation and measurement results demonstrate the capability of the proposed metasurface to generate reconfigurable OAM beams with high purity, indicating the application potentials of proposed meta-devices in future OAM communications.